THE EFFECTIVENESS OF DIGITAL EVIDENCE IN E-COMMERCE DISPUTE LITIGATION IN THE DIGITAL ERA - Febrina Artia Putri; Nabitatus Sa’adah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of digital commerce, while offering convenience and positive impacts, also has the potential to trigger legal disputes between related parties. In the litigation process of digital commerce, digitally presented evidence such as emails, instant messages, and electronic payment records becomes crucial in proving the truth of a legal event. This article specifically examines the effectiveness of electronic evidence in resolving digital trade disputes in Indonesia. Using a normative juridical approach, this study finds that although digital evidence is recognized under the Electronic Information and Transactions (ITE) Law, its implementation still faces several challenges in terms of validity and integrity. Therefore, strengthening regulations, increasing public awareness, and enhancing the capacity of competent law enforcement officials are essential to ensure justice and effectiveness in resolving digital commerce disputes.